Penerapan Model Pembelajaran Kooperatif Tipe TGT (Teams Games Tournaments) Terhadaphasil Belajar dan Motivasi Belajar Siswa - Vivin Gusdiana; Villia Anggraini; Ramadoni Ramadoni (Departement of Mathematics Education, 2023)
This research was motivated by the low learning outcomes and learning motivation of grade VIII students of SMPN 1 IV Jurai, Pesisir Selatan Regency. The purpose of this study was to determine the influence of the application of the Teams Games Tournaments learning model on mathematics learning outcomes and motivation of grade VIII students of SMPN 1 IV Jurai, Pesisir Selatan Regency. The type of research used in this study is experimental research with research design is post-test only control group design. The population of this study was all grade VIII students of SMPN 1 IV Jurai, South Coast District. The sampling technique used in this study was random sampling so that class VIII4 was selected as an experiment class with twenty-one students and class VIII1 as a control class with twenty-two students. The instruments used are learning outcomes tests and student learning motivation questionnaires.